A Theoretical Framework for Informal 3D Rendered Analysis of the Roman Lararium from Apollonia-Arsuf - Schoueri, Kelly Gillikin; Teixeira-Bastos, Marcio [UNESP] (De Gruyter Poland Sp Z O O, 2021)
Digital reconstruction and visualization of archaeological sites are beneficial not only for public edification and admiration, but they can also significantly contribute to the site interpretation process. By going beyond basic modeling scenarios, one can apply 3D analyses for accurately testing visibility and lighting parameters, among other aspects. Based on the results of these tests, further insights can be extrapolated about the lived experience of culturally specific ancient peoples. The case of a Roman villa at Apollonia-Arsuf in Israel presents the opportunity to apply these informal techniques to a household shrine, or niche-style lararium, found within the building in order to ascertain sightline visibility based on the architectural plan and visual impact as a result of artificial illumination from ceramic lamps. This paper also considers how photorealistic visualizations aid in phenomenological areas of research through sensory archaeology and sense of place, which in turn encourages reflection on the political, social, and religious meanings of the built environment. When we combine the power and diverse applications of 3D visualization technology with decades of research about Roman architecture, culture, religion, and social norms, the result is a step closer to recreating archaeological remnants and, in turn, understanding the ancient experience.
Keywords: 3D visualization; visibility analysis; illumination; sensory archaeology; Roman Israel